2010
DOI: 10.1002/ab.20372
|View full text |Cite
|
Sign up to set email alerts
|

Media depictions of physical and relational aggression: connections with aggression in young adults' romantic relationships

Abstract: Various studies have found that viewing physical or relational aggression in the media can impact subsequent engagement in aggressive behavior. However, this has rarely been examined in the context of relationships. Accordingly, the aim of this study was to examine the connection between viewing various types of aggression in the media and perpetration of aggression against a romantic partner. A total of 369 young adults completed a variety of questionnaires asking for their perpetration of various forms of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Recent empirical work has found that engaging with popular culture depicting violence against women is associated with attitudes toward and experiences of sexual violence and intimate partner violence (Bonomi et al, ; Coyne et al, ; Hernandez, Weinstein, & Munoz‐Labay, ). For example, emerging adult women who read the Fifty Shades of Grey novels (James, ) are more likely than nonreaders to experience verbal abuse and stalking by a romantic partner (Bonomi et al, ).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Recent empirical work has found that engaging with popular culture depicting violence against women is associated with attitudes toward and experiences of sexual violence and intimate partner violence (Bonomi et al, ; Coyne et al, ; Hernandez, Weinstein, & Munoz‐Labay, ). For example, emerging adult women who read the Fifty Shades of Grey novels (James, ) are more likely than nonreaders to experience verbal abuse and stalking by a romantic partner (Bonomi et al, ).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…For example, emerging adult women who read the Fifty Shades of Grey novels (James, ) are more likely than nonreaders to experience verbal abuse and stalking by a romantic partner (Bonomi et al, ). Likewise, emerging adults exposed to relational aggression in the media are prone to experience romantic relational aggression (Coyne et al, ), and those exposed to violence against women in hip‐hop culture tend to minimize interpersonal violence (Hernandez et al, ). Kahlor and Eastin () similarly showed that soap‐opera viewing is positively correlated with rape myth acceptance.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Individuals may find this level of engagement through discussion combined with limits on time and content, to be intrusive or coercive and families may be resistant. It is reasonable to suspect that communications and media exposure will be a factor in developing attitudes toward aggression in relationships, emerging attitudes toward sexual behavior, as well as stimulate consumer cravings that may shape a child's career choice and life satisfaction (Brown, Keller, & Stern, 2009;Coyne, et al, 2011;Shrum, Lee, Burroughs, & Rindfleisch, 2011).…”
Section: Technology Use Among School-age Childrenmentioning
confidence: 99%
“…Normalization of violence against women in popular fiction D espite known associations between consumption of media containing violence and related risk factors, including television and print media, and aggression tendencies, [1][2][3][4][5] along with theories suggesting that consumption of fictional communication can alter beliefs and attitudes, [6][7][8][9][10][11] no prior study has empirically characterized the association between health risks and reading popular fiction depicting violence against women. Fifty Shades-one of the world's fastest selling fiction series comprising Fifty Shades of Grey, Fifty Shades Darker, and Fifty Shades Freed 12-14 depicts problematic violence against women 15,16 cloaked within the romantic and erotic bondage-discipline-sadism-masochism [17][18][19] relationship involving Christian Grey and Anastasia Steele.…”
Section: Introductionmentioning
confidence: 99%